Effects of 5-HT released from platelets on thrombin-induced aggregation and ATP release in rabbit platelets in vitro - Li Bai-Yan; Li Wen-Han (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of arachidonic acid (AA)-induced endogenous serotonin (5-HT) release on platelet aggregation and ATP release by thrombin (Thr). METHODS: Platelet aggregation and release reaction were quantified by light transmission in platelet-rich-plasma (PRP) and the amount of ATP in medium. The effects of endogenous 5-HT were evaluated by the filtration of content in cuvette A (content A) containing endogenous 5-HT into cuvette B in which Thr-induced aggregation was observed in the absence/presence of ¿(+/-)-5 (Z)-7-[3-endophenylsulfonylamino [2.2.1] bicyclohept-2-exo-yl]heptanoic acid, sodium salt¿ (S-145) or/and methysergide (Met). RESULTS: (1) AA 100 and 200 mumol.L-1 induced aggregation and ATP release in cuvette A. When the aggregation reached a peak, the content A directly caused platelet aggregation in cuvette B, and it was inhibited by S-145 100 nmol.L-1, Met 30 mumol.L-1, and inhibited more potently by S-145 + Met. (2) In the presence of S-145 100 nmol.L-1 in cuvette B, aggregations by Thr 0.1 and 0.3 IU.L-1 were enhanced (P < 0.01) by the filtrate, while Thr 0.5 IU.L-1-caused ATP release was suppressed (P < 0.01) without the effect on aggregation. Preincubation with S-145 and Met, the effects of the filtrate on aggregation and ATP release were abolished. (3) By prolongation of the time intervals between filtration and addition of Thr, the aggregation was enhanced and ATP release was reduced. CONCLUSION: Endogenous 5-HT was released from activated platelet and plays, in turn, a role in the regulation of platelet aggregation by the superimposition of cytosolic-free calcium ([Ca2+]i) and the feedback loop to regulate release reaction and calcium.